Research on control plane technology for wide-area deterministic networking - Hongwei SHI; Qingqiang CHEN; Zhiwei CHENG; Tao HUANG (Dianxin kexue)
The efficient allocation of data elements is particularly important for achieving digital transformation in traditional industries.Network supply capabilities not only require low latency and high bandwidth for data packets, but also require low jitter and certainty in data packets.Deterministic networking technology is the key to build lossless, reliable, and deterministic wide-area communication capabilities.The key control technologies and design concepts for wide-area deterministic networking were proposed, and the specific plans for achieving deterministic networking perception, service planning, and traffic scheduling were elaborated on.Through experimental verification and application testing, the effectiveness of the system structure is proven and it meets the management and scheduling needs of deterministic networking.